COVID-19: Known & Unknown Facts - Rakesh Tank; Priyanka Tank (Disease and Health: Research Developments Vol. 2, 2024)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has significantly reshaped global health systems, economies, and societal dynamics. Since its emergence in late 2019, extensive research has shed light on various aspects of the virus and its impact. Known facts about COVID-19 include its zoonotic origin, primarily attributed to wildlife-to-human transmission; its high transmissibility through respiratory droplets, aerosols, and contaminated surfaces; and its ability to cause a spectrum of disease severity ranging from asymptomatic infections to life-threatening complications like acute respiratory distress syndrome (ARDS). The development and distribution of vaccines have been pivotal in mitigating the severity of outbreaks and reducing mortality rates. Treatments such as antiviral drugs, monoclonal antibodies, and supportive care have also improved patient outcomes. Despite these advances, numerous unknowns persist. These include the exact origins of the virus, the mechanisms behind long-term effects such as “long COVID,” and the virus’s ability to mutate into more virulent or vaccine-resistant variants. Furthermore, questions remain regarding the duration of vaccine-induced immunity, the virus’s interaction with pre-existing chronic conditions, and the societal and psychological impacts of prolonged pandemic conditions. By consolidating the known and unknown facts about COVID-19, this chapter aims to provide a comprehensive understanding of the disease’s multifaceted nature and inform public health policies worldwide.